Facial Nerve Injury after Extracapsular Dissection for Benign Parotid Tumors with and without Intraoperative Monitoring: A Retrospective Study of a Single Center - Maria Giulia Cristofaro; Walter Colangeli; Francesco Ferragina; Giuseppe Tarallo; Angelo Ruggero Sottile; Maria Grazia Ioppolo; Antonella Arrotta; Ida Barca (Diagnostics)
Background: Facial nerve injury (FNI) is the most common complication of parotid surgery and manifests as FN paralysis. The use of intraoperative facial nerve monitoring (IFNM) is becoming an established intraoperative aid for surgeons, assisting in the identification of the location and dissection of the facial nerve trunk or branches. The postoperative outcomes of parotid surgery with and without monitoring have been addressed in only a limited number of studies. Objective: The objective of this study is to evaluate the incidence of postoperative paralysis in patients undergoing extracapsular dissection (ED) for benign parotid tumors concerning the use or non-use of IFNM. Materials and Methods: The retrospective study was conducted at the Maxillo-Facial Department of the Magna Graecia University of Catanzaro. The patients were divided into two groups: Group 1 consisted of patients who underwent surgery without IFNM (1 January 2015 to 31 December 2018); Group 2, on the other hand, consisted of patients who underwent surgery with IFNM (1 January 2019 to 31 December 2022). Group 2 employed the Nerve Integrity Monitor (Medtronic’s NIM®). To classify the FN function, we employed the modified House–Brackmann classification system. To evaluate the dependence between the “use of IFNM” and “postoperative paralysis”, a descriptive analysis was conducted, including applying the Chi-squared test and calculating the Pearson correlation. Subsequently, a binary logistic regression model was applied to further evaluate the correlation between the latter. The level of statistical significance was set at p < 0.05. Results: A total of 276 patients were included in the study: 120 subjects were assigned to Group 1 (43.5%, comprising 60 men and 60 women) and 156 subjects were assigned to Group 2 (56.5%, comprising 93 men and 63 women). In 91.7% of the cases (n. 253, precisely 105 in Group 1 and 148 in Group 2), no FNI occurred. In 8.33% of the cases (n. 23, specifically 15 in Group 1 and 8 in Group 2), postoperative paralysis was observed. Of these subjects, only two in Group 1 had permanent paralysis (8.69%); therefore, 91.31% had transient paralysis. As a result, 91.31% of the subjects exhibited transient paralysis. In the case of FNI, 78% of the cases involved the marginal mandibular branch (n. 18), 13% involved the temporo-zygomatic branch (n. 3), and 7% involved more than one branch (n = 2). The results of the multivariable binary logistic regression analysis demonstrated that the use of IFNM was a statistically significant influencing factor, with an estimated reduction in postoperative paralysis of approximately 62% (OR 0.378; 95% CI: 0.155–0.92). In Group 2, the occurrence of transient complications was significantly reduced (OR 0.387; 95% CI: 0.149–1.002 with p < 0.05). Discussion and Conclusions: The use of IFNM in the ED for benign parotid tumors significantly reduces the rate of FNI and, consequently, postoperative FN paralysis. On the other hand, the use of monitoring systems must not replace the experience and anatomical knowledge of the surgeon.